2010
DOI: 10.1074/jbc.m110.136903
|View full text |Cite
|
Sign up to set email alerts
|

NMR and Bioinformatics Discovery of Exosites That Tune Metalloelastase Specificity for Solubilized Elastin and Collagen Triple Helices

Abstract: The catalytic domain of metalloelastase (matrix metalloproteinase-12 or MMP-12) is unique among MMPs in exerting high proteolytic activity upon fibrils that resist hydrolysis, especially elastin from lungs afflicted with chronic obstructive pulmonary disease or arteries with aneurysms. How does the MMP-12 catalytic domain achieve this specificity? NMR interface mapping suggests that ␣-elastin species cover the primed subsites, a strip across the ␤-sheet from ␤-strand IV to the II-III loop, and a broad bowl fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(62 citation statements)
references
References 91 publications
2
60
0
Order By: Relevance
“…Apart from the Hpx domains of collagenases, examples include the fibronectin type II repeats in MMP-2 and MMP-9, which contribute to the binding and degradation of elastin, gelatin, and type IV collagen (47). Recent NMR and mutagenesis studies of the Cat domain of MMP-12 characterized several exosites for elastin (48,49). Similar studies were carried out with the isolated Hpx domain of MMP-1 and a triple-helical collagen peptide (40) and suggested a role for Phe282 (Phe301 in the numbering used in ref.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the Hpx domains of collagenases, examples include the fibronectin type II repeats in MMP-2 and MMP-9, which contribute to the binding and degradation of elastin, gelatin, and type IV collagen (47). Recent NMR and mutagenesis studies of the Cat domain of MMP-12 characterized several exosites for elastin (48,49). Similar studies were carried out with the isolated Hpx domain of MMP-1 and a triple-helical collagen peptide (40) and suggested a role for Phe282 (Phe301 in the numbering used in ref.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-1 residue 210 (and the corresponding residue in MMP-8) facilitates collagenolytic and triple-helical peptidase activities (8,46). When studying macrophage elastase (MMP-12) interactions with triple-helical substrates by NMR spectroscopy, several CAT domain exosites were identified and localized (47,48). For example, analyzing MMP-12 alone or in complex with the ␣1(V)436 -450 THP showed interactions located far from the catalytic cleft; more than 30 residues total were altered from the uncomplexed enzyme, especially Asp-124, Asp-164, and .…”
Section: Discussionmentioning
confidence: 99%
“…However, MMP-12 cannot have the same extended interactions with substrate as MMP-2 and MMP-9 because MMP-12 does not possess the fibronectin type II inserts that MMP-2 and MMP-9 utilize to bind collagens (1). Prior studies showed that the MMP-12 catalytic domain possesses collagenolytic activity (57), and this domain provides contacts outside of the active site cleft (exosites) that participate in collagenolysis (58,74). As one of the proposed contacts involves Lys 241 of MMP-12, its interactions with charge clusters might differ from those of the collagenases (MMP-1, MMP-8, MMP-13, and MT1-MMP) and gelatinases (MMP-2 and MMP-9).…”
Section: Nomentioning
confidence: 99%